Animal models for transplant immunology: bridging bench to bedside - Minseok Kang; Hwon Kyum Park; Kyeong Sik Kim; Dongho Choi (Clinical Transplantation and Research)
The progress of transplantation has been propelled forward by animal experiments. Animal models have not only provided opportunities to understand complex immune mechanisms in transplantation but also served as a platform to assess therapeutic interventions. While small animals have been instrumental in uncovering new therapeutic concepts related to immunosuppression and immune tolerance, the progression to human trials has largely been driven by studies in large animals. Recent research has begun to explore the potential of porcine organs to address the shortage of available organs. The consistent progress in transplant immunology research can be attributed to a thorough understanding of animal models. This review provides a comprehensive overview of the available animal models, detailing their modifications, strengths, and weaknesses, as well as their historical applications, to aid researchers in selecting the most suitable model for their specific research needs.